Fabrication of digital parabolic motion experiments set based on the ATMEGA328 microcontroller to measure motion parameters - Farah Sarjani; Yohandri Yohandri; Zulhendri Kamus (PILLAR OF PHYSICS, 2017)
Technological developments have produced many tools that can facilitate human work in industrial and scientific needs. In addition, electronics has also produced sophisticated components, both in the manufacture of measurement systems and experimental set-making system. This research created a set of digital parabolic motion experiment that display the value of time, speed and distance of objects. The purpose of this research is to know the performance and design spesifications a set of digital parabolic motion experiment using photogate and vibration sensors based on ATMega328 microcontroller to measure the parameters of motion. This research is a laboratory experiment. The measurement technique used is direct and indirect measurements. Direct measurement made to determine the value of time, speed and distance of objects that display on the LCD. Indirect measurement is made to determine the accuracy and precision of digital parabolic motion experimental set system. Analysis of measurement results can be explained that there are two important results from this research. First, the result of the measurement system design consist of launcher made from the photogate and vibration sensors as the sense of object (projectile) passing through the sensor. Second, set of digital parabolic motion experiment has a precise value that can be determined from the percentage of error between the actual value